2022
DOI: 10.35848/1347-4065/ac4142
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of amyloid fibril formation by multichannel sonochemical reactor

Abstract: Formation of amyloid fibrils of various amyloidogenic proteins is dramatically enhanced by ultrasound irradiation. For applying this phenomenon to the study of protein aggregation science and diagnosis of neurodegenerative diseases, a multichannel ultrasound irradiation system with individually adjustable ultrasound-irradiation conditions is necessary. Here, we develop a sonochemical reaction system, where an ultrasonic transducer is placed in each well of a 96-well microplate to perform ultrasonic irradiatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Acoustic cavitation bubbles generated by intense ultrasound in water radiate secondary ultrasound called acoustic cavitation noise owing to their volumetric oscillation. [1][2][3][4][5] In sonochemistry, which is concerned with understanding the chemical effects associated with acoustic cavitation phenomena, [6][7][8][9][10][11] acoustic cavitation noise has been attracting attention as a method for monitoring acoustic cavitation conditions, and numerous research findings have been reported. [12][13][14][15][16][17] However, reports on the explicit use of acoustic cavitation noise other than monitoring are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic cavitation bubbles generated by intense ultrasound in water radiate secondary ultrasound called acoustic cavitation noise owing to their volumetric oscillation. [1][2][3][4][5] In sonochemistry, which is concerned with understanding the chemical effects associated with acoustic cavitation phenomena, [6][7][8][9][10][11] acoustic cavitation noise has been attracting attention as a method for monitoring acoustic cavitation conditions, and numerous research findings have been reported. [12][13][14][15][16][17] However, reports on the explicit use of acoustic cavitation noise other than monitoring are limited.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Therefore, numerous attempts have been made to apply this phenomenon to various applications. [7][8][9][10][11][12] The radiation of shockwaves due to vibration, one of the mechanical effects of bubbles, results in acoustic emission called acoustic cavitation noise. The acoustic cavitation noise frequency spectrum reflects the bubbles' vibration state.…”
Section: Introductionmentioning
confidence: 99%